A comparison of longitudinal [18F]GTP1 tau pet with other imaging and cognitive endpoints in the Tauriel Phase II Study. (1st February 2022) - Manser, Paul T.; Sanabria‐Bohorquez, Sandra; Wildsmith, Kristin R.; Toth, Balazs; Blendstrup, Mira; Pickthorn, Karen; Teng, Edmond
Abstract: Background: The Tauriel Study (NCT03289143) was a Phase 2 randomized, double‐blind, placebo‐controlled, parallel‐group clinical trial that assessed the safety and efficacy of semorinemab in patients with prodromal‐to‐mild Alzheimer's disease over 73 weeks. We sought to assess the longitudinal performance of tau PET imaging and to determine the relationships between the multiple imaging and cognitive endpoints that were collected. Method: Cognitive testing, [ 18 F]GTP1 PET, and volumetric MRI imaging were performed at baseline, Week 49 and Week 73. Relationships between imaging and cognitive endpoints were assessed with Spearman correlations. Standardized change from baseline among imaging and cognitive endpoints were compared using Cohen's D. Result: 375 participants had evaluable [18F]GTP1 tau PET scans at baseline. On average, [18F]GTP1 SUVR in a temporal metaROI (mean = 1.56, SD = 0.28) was significantly higher than SUVR in whole cortical gray matter (mean = 1.33, SD = 0.25). In spite of the heterogenous localization of baseline [18F]GTP1 signal within and across subjects, longitudinal changes in tau PET were spatially more uniform: whole cortical gray SUVR and temporal meta ROI performed similarly at Week 73 in terms of standardized longitudinal change (Cohen's D = 0.61 and 0.65, respectively). Furthermore, correlations between local baseline SUVR, as parcellated across cortical Hammers Atlas ROIs, and change from baseline to week 73 were low (Avg Spearman r = 0.14, range = [‐0.34, 0.37]). Conclusion: The Tauriel trial successfully enrolled a prodromal‐to‐mild AD patient population that progressed on both clinical and imaging endpoints that were statistically sensitive to detect potential treatment effects. However, correlations between changes in imaging and cognitive endpoints were low. Longer observation periods may further elucidate the associations between imaging and clinical endpoints.